2007
DOI: 10.1358/mf.2007.29.3.1075351
|View full text |Cite
|
Sign up to set email alerts
|

Antiaggressive effects of topiramate in agonistic encounters between male mice

Abstract: Topiramate, an antiepileptic drug, has been found to be useful for the treatment of aggression in clinical populations. However, no studies have explored the action of this compound on aggressive behavior in laboratory animals. This work examined the effects of topiramate (10, 20, 40 and 80 mg/kg, i.p.) on agonistic interactions between male mice, using an ethopharmacological approach. Individually housed mice were exposed to anosmic "standard opponents" 30 min after drug administration. Ten minutes of diadic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Several GABA-modulating drugs, in particular those used as antiepileptics, have shown promise as anti-aggressive agents in both non-humans (Navaro et al, 2007; Rogers and Depaulis, 1982) and humans who are at higher than normal risk for aggressive behavior (Guay 2007; Stanford et al, 2005; Nickel and Loew, 2008). It has been suggested that the mechanism for these anti-aggressive effects may be an interaction of (a) the individual organism’s history of aggressive behavior and (b) available levels of CNS GABA, which putatively serve an inhibitory function in modulating other receptor systems (DA and 5-HT) and prefrontal-limbic circuits active during bouts of aggressive behavior (Bjork, 2001; Miczek et al, 2003; Siever, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several GABA-modulating drugs, in particular those used as antiepileptics, have shown promise as anti-aggressive agents in both non-humans (Navaro et al, 2007; Rogers and Depaulis, 1982) and humans who are at higher than normal risk for aggressive behavior (Guay 2007; Stanford et al, 2005; Nickel and Loew, 2008). It has been suggested that the mechanism for these anti-aggressive effects may be an interaction of (a) the individual organism’s history of aggressive behavior and (b) available levels of CNS GABA, which putatively serve an inhibitory function in modulating other receptor systems (DA and 5-HT) and prefrontal-limbic circuits active during bouts of aggressive behavior (Bjork, 2001; Miczek et al, 2003; Siever, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…-Higher doses (e.g. 0.8 mg/kg) produce a significant elevation in defense/submission, avoidance/fleeing, and social investigation behaviors [276].…”
Section: Discussionmentioning
confidence: 99%
“…Quinpirole administration has been used in rats and mice to model psychiatric disorders, such as obsessive-compulsive disorder and schizophrenia. After exposure, the animals presented anxiety-like behavior and elevated stereotypic and erratic movements (Hoffman, 2011;Kostrzewa et al, 2016;Navarro & Maldonado, 1999;Nielsen et al, 2017;Sams-Dodd, 1998;Szechtman et al, 2017). Additionally, only a few studies have reported alterations in social and aggressive behavior (Maple et al, 2017;Sams-Dodd, 1998;Szechtman et al, 2017).…”
Section: Quantification Of Neurotransmitter Levelsmentioning
confidence: 99%